2020
DOI: 10.1108/itp-03-2020-0117
|View full text |Cite
|
Sign up to set email alerts
|

Information confusion and intention to stop using social networking site: a moderated mediation study of psychological distress and perceived novelty

Abstract: PurposePeople are living in a very rich and diversified information world. However, they are facing an explosion of information on social networking site (SNS) bombarding them every day. People get confused when they expose to similar, overloaded, ambiguous and misleading information. Unfortunately, the effect of information confusion on users' psychological outcome and behavioral intention has been absent in prior literature. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 43 publications
3
46
0
6
Order By: Relevance
“…This finding implies that employees tend to feel tired, stressed, depressed, and even angry when they perceive their jobs to be insecure ( Baum et al, 2020 ; Vo-Thanh et al, 2021 ; Vo-Thanh, Vu, et al, 2022 ). In this case, negative emotions and feelings of depression reduce employees' motivation at work, and they are more likely to engage in negative behaviors because they look for ways to cope with the discomfort and unpleasant feelings ( Dang, 2020 ). This finding provides support for Bajrami et al (2021) , Meyer et al (2021) , and Wong et al (2021) who suggested that employees often feel negative emotions and engage in negative behaviors during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding implies that employees tend to feel tired, stressed, depressed, and even angry when they perceive their jobs to be insecure ( Baum et al, 2020 ; Vo-Thanh et al, 2021 ; Vo-Thanh, Vu, et al, 2022 ). In this case, negative emotions and feelings of depression reduce employees' motivation at work, and they are more likely to engage in negative behaviors because they look for ways to cope with the discomfort and unpleasant feelings ( Dang, 2020 ). This finding provides support for Bajrami et al (2021) , Meyer et al (2021) , and Wong et al (2021) who suggested that employees often feel negative emotions and engage in negative behaviors during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…According to Dang (2020, p. 1430) , psychological distress refers to “an emotional state that reflects unpleasant feelings and discomfort experiences”. Specifically, psychological distress reflects a state of emotional suffering characterized by symptoms of anxiety and depression ( Arvidsdotter, Marklund, Kylén, Taft, & Ekman, 2016 ).…”
Section: Context Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Kemudian menurut (M. Karani et al, 2021) Psychological Distress dapat didefinisikan sebagai "istilah umum yang mencakup stres, malaise, depresi, kecemasan, dan masalah kesehatan mental terkait lainnya". Sumber lain mengatakan bahwa Psychological Distress adalah kondisi emosional yang mencerminkan perasaan tidak menyenangkan dan kecemasan (Dang, 2020).…”
Section: Psychological Distressunclassified
“…Beberapa faktor, seperti faktor lingkungan, faktor pekerjaan, faktor privasi atau kehidupan pribadi, dan faktor sosial, diketahui sebagai pemicu Psychological Distress (Dang, 2020). Karena Psychological Distress, kecemasan, atau depresi terkait secara kognitif, otak pegawai yang terancam mematikan proses berpikir yang kompleks dan berfokus pada emosi yang berlawanan (Kalyar et al, 2020).…”
Section: Psychological Distressunclassified